2019
DOI: 10.1007/s40995-018-00672-3
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Properties of Discrete Klein–Gordon s-Wave Equation with Quadratic Eigenparameter-Dependent Boundary Condition

Abstract: In this study, we consider the spectral analysis of the boundary value problem (BVP) consisting of the discrete Klein-Gordon equation and the quadratic eigenparameter-dependent boundary condition. Presenting the Jost solution and Green's function, we investigate the finiteness and other spectral properties of the eigenvalues and spectral singularities of this BVP under certain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Spectral analysis of difference equations provides a lot of information about these equations. As a result, there are many studies on the spectral analysis of discrete operators generated by difference equations recently (Yokus and Coskun, 2019;Yokus and Coskun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Spectral analysis of difference equations provides a lot of information about these equations. As a result, there are many studies on the spectral analysis of discrete operators generated by difference equations recently (Yokus and Coskun, 2019;Yokus and Coskun, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…He also showed that these eigenvalues and spectral singularities are of finite number with finite multiplicities under certain conditions. Later developments in this area concerned spectral analysis of the boundary value problems of the differential and discrete operators including Sturm-Liouville, Klein-Gordon, quadratic pencils of Schrödinger and Dirac-type operators within the context of determination of Jost solution and providing suffcient conditions guaranteeing the finiteness of the eigenvalues and spectral singularities [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Note that investigation of discrete analogues of ordinary differential operators is an important research area since difference equtions are well suited to find solutions with the aid of computers and can model many contemporary problems arising in control theory, biology, and engineering [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%